Factors Affecting Controlled Blood Sugar Levels in Patients with Type 2 Diabetes Mellitus at the Internal Medicine Polyclinic at the Regional General Hospital of West Nusa Tenggara Province - I Wayan Mustika Maha Putra; Catarina Budyono; Ardiana Ekawanti; Joko Anggoro (Jurnal Biologi Tropis, 2023)
Indonesia is ranked seventh out of countries that contributed to the highest number of DM in the world in 2019 and estimate that in 2045 it could reach 16.6 million cases. West Nusa Tenggara Province is one of the provinces with a fairly high DM rate reaching 21,308 with various complications due to uncontrolled blood sugar levels. High blood sugar levels in DM patients are caused by several uncontrolled factors in DM patients. This study aims to determine the factors associated with uncontrolled blood sugar levels in type 2 DM patients at the NTB Provincial Hospital. This research is a observational with a cross sectional study. The sample selection using the consecutive sampling obtained from the medical records of type 2 DM patients who were treated at the Internal Medicine Polyclinic of the NTB Provincial Hospital. The study sample size were 100 people with univariate and bivariate data analysis using the Chi-square test. The subjects in this study were dominated by patient age > 45 years (75.6%), female (51.2%), using non-insulin therapy (52.4%), and duration of type 2 diabetes < 10 years. (67.07%) with uncontrolled blood sugar status (52.4%). Bivariate analysis using the Chi-square showed that there were a statistically significant relationship between controlled blood sugar levels and patient age (p=0.021), controlled blood sugar levels with gender (p=0.008), controlled blood sugar levels and the type of therapy (p=0.008). = 0.004), and controlled blood sugar levels with duration of diabetes (0.023).